Consumer Standards as a Strategic Device to Mitigate Ratchet Effects in Dynamic Regulation - Raffaele Fiocco; Roland Strausz (Center for Economic Studies and ifo Institute (CESifo), 2014)
Strategic delegation to an independent regulator with a pure consumer standard improves dynamic regulation by mitigating ratchet effects associated with short term contracting. A pure consumer standard alleviates the regulator's myopic temptation to raise output after learning the firm is inefficient. Anticipating this tougher regulatory behavior, efficient firms find it less attractive to exaggerate costs. This reduces the need for long term rents and mitigates ratchet effects. A welfare standard biased towards consumers entails, however, allocative costs arising from partial separation of the firms' cost types. A trade-off results which favors strategic delegation when efficient firms are relatively likely.
Keywords: D82; L51; 330; dynamic regulation; strategic delegation; consumer standard; ratchet effects; limited commitment